Community health workers perspective on the COVID-19 impact on primary health care in Northeastern Brazil - Anya Pimentel Gomes Fernandes Vieira-Meyer; Franklin Delano Soares Forte; José Maria Ximenes Guimarães; Sidney Feitoza Farias; André Luiz Sá de Oliveira; Maria Socorro de Araújo Dias; Claudete Ferreira de Souza Monteiro; Fernando José Guedes da Silva Júnior; Ana Patrícia Pereira Morais; Maria Rosilene Candido Moreira; Márcia C. Castro; Aisha Khizar Yousafzai (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
Abstract: This article evaluates the COVID-19 pandemic impacts on the Family Health Strategy (FHS) team's work routines across a range of northeast Brazilian cities as perceived by community health workers (CHW). Data on COVID-19, CHW activities, and FHS teams were collected in 2021 by a structured questionnaire. A total of 1,935 CHWs from four state capitals (Fortaleza - Ceará State, João Pessoa - Paraíba State, Recife - Pernambuco State, Teresina - Piauí State) and four hinterland cities (Crato, Juazeiro do Norte, Barbalha, Sobral - Ceará State) participated in the study. Most CHWs were women (82.42%), with mean age 46.25±8.54 years. Many (39.92%) were infected with COVID-19, of which 70.78% believed they were infected in the workplace. A total of 77.82% defined their role as frontline in the fight against COVID-19, 16.07% reported receiving training for COVID-19, and 13.74% had access to sufficient protective equipment. Most (90.27%) believed their work routines were modified by the pandemic, either strengthening (41.46%) or weakening (44.41%) the team spirit. Home visits (60.55%), health promotion actions in schools (75.66%) and in specific community groups (93.96%), and other on-site community services (66.01%) showed a reduction in frequency. The sampled cities revealed a significant heterogeneity regarding responses to the COVID-19 pandemic, possibly associated with a lack of coordination by the Federal Government. Regardless of context, the pandemic led to a reconfiguration of local health systems, workflows, and primary care protocols for FHS teams. The importance of the Brazilian Unified National Health System (SUS) and its potential for reorganization during crisis should be acknowledged while preserving the headway made thus far.